2014
DOI: 10.1371/journal.pone.0102161
|View full text |Cite|
|
Sign up to set email alerts
|

Anti-Epileptic Effect of Ganoderma Lucidum Polysaccharides by Inhibition of Intracellular Calcium Accumulation and Stimulation of Expression of CaMKII α in Epileptic Hippocampal Neurons

Abstract: PurposeTo investigate the mechanism of the anti-epileptic effect of Ganoderma lucidum polysaccharides (GLP), the changes of intracellular calcium and CaMK II α expression in a model of epileptic neurons were investigated.MethodPrimary hippocampal neurons were divided into: 1) Control group, neurons were cultured with Neurobasal medium, for 3 hours; 2) Model group I: neurons were incubated with Mg2+ free medium for 3 hours; 3) Model group II: neurons were incubated with Mg2+ free medium for 3 hours then culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 37 publications
1
31
0
Order By: Relevance
“…CACNB4 could directly couple electrical activity to gene expression, which was responsible for a type of juvenile myoclonic epilepsy[76]. Recent studies had shown that ganoderma lucidum polysaccharides may inhibit calcium overload and promote CaMK II α expression to protect epileptic neurons[77]. …”
Section: Discussionmentioning
confidence: 99%
“…CACNB4 could directly couple electrical activity to gene expression, which was responsible for a type of juvenile myoclonic epilepsy[76]. Recent studies had shown that ganoderma lucidum polysaccharides may inhibit calcium overload and promote CaMK II α expression to protect epileptic neurons[77]. …”
Section: Discussionmentioning
confidence: 99%
“…CaMKII is a multifunctional serine/threonine protein kinase in neurons that is involved in regulating neurotransmission and synaptic plasticity in response to neuronal activity-induced calcium signaling 9 . CaMKII-mediated modulation of neuronal sodium current has effect on neuronal excitability in epilepsy 10 , and its inactivation is associated with many experimental models of epilepsy 11 , 12 . CaKMII activity at synapses is associated with epileptogenesis, as well as other changes in the synapse that are related to glutamate receptor activation 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Glycans consists of arabinose, mannose, fucose, galactose, xylose, glucuronic acid and also glucose [17]. The other pharmacological properties of polysaccharides were reported such as, hepatoprotective [18], neuroprotective effect [19], anti-amnesic effect [20], anti-epileptic effect [21], anti-obesity effect [22], anti-depressant [23], anti-microbial [24][25][26], anticancer effect [27,28] and ant diabetic [29].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%